Accounting Standards for Complex Resources of International Organizations. (August 2017) - Bergmann, Andreas; Fuchs, Sandro
Abstract: This article will describe the implementation of International Public Sector Accounting Standards (IPSAS) in UN System Organizations and consider technically controversial issues such as revenue recognition in more detail. Based on the IPSAS financial statements of 24 UN System Organizations, the article provides an overview about current funding schemes and key issues related to conditional contributions. Results show a heterogeneous funding mix for UN System Organizations while, overall, voluntary contributions remain the most important revenue source. The main accounting implication arises from conditional voluntary contributions with specified performance obligations, requiring an entity to defer revenue and recognize a liability. Although all analysed UN System Organizations report under the same accounting principles, there exist differences in the level of information concerning conditional contributions and outstanding performance obligations. The article concludes that IPSAS bears the capacity to increase overall financial accountability and to trigger management debates about issues such as resource dependency, topics being discussed by other contributions in this special issue. Overall it is argued that IPSAS shall not be seen as a mere technical exercise, but as a management tool to ensure a flexible funding scheme to successfully achieve an entity's long‐term objectives. Abstract : Overall it is argued that IPSAS shall not be seen as a mere technical exercise, but as a management tool to ensure a flexible funding scheme to successfully achieve an entity's long‐term objectives.